Error Analysis in German Language Teachers and Learners - Rafarda Ajeng Septiardhya (Eduvest - Journal of Universal Studies, 2024)
This research seeks to reveal the errors displayed by German language teachers and learners. Therefore, the researcher will investigate what types of errors appear in the German language learning process of teachers and learners and what error levels appear in the German language learning process of teachers and learners. The researcher uses error level analysis (James, 2013) divided into 3 main parts, namely substance errors, textual errors, and discourse errors. The results prove that substance errors and textual errors are found in the teacher. The substance errors are coding errors when speaking (mispronunciations) and decoding errors in reading (miscues). While the textual errors are errors in composing spoken text (misspeaking) and errors in composing written text (miswriting). Then, substance errors, textual errors, and discourse errors appear in the learners. In substance errors, there are coding errors in speaking (mispronunciations), coding errors in writing (misspellings), decoding errors in listening (misperceptions) and decoding errors in reading (miscues). In textual errors, errors in understanding spoken text (mishearing), and errors in understanding written text (misreading) were found. In discourse errors, errors in formulating oral discourse (misrepresenting) were found. Of the many errors, both teachers and learners excel in mispronunciations and misspeaking. Both need to hone their knowledge of the target language more deeply.